2007
DOI: 10.4028/www.scientific.net/ddf.266.149
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Intermetallic Phases in U-Mo vs. Al Alloy Diffusion Couples Annealed at 550°C

Abstract: This study examined the growth kinetics of intermetallic phases that develop in solid-tosolid diffusion couples assembled with U-7, 10 and 12wt.%Mo vs. Al alloys (Al, Al-2wt.%Si, Al- 5wt.%Si, 4043 and 6061) after a diffusion anneal at 550°C for 24 hours. Based on interdiffusion microstructure and integrated interdiffusion coefficients, the addition of Si into the Al matrix alloy was observed to significantly reduce the growth rate of the intermetallic layer that primarily consisted of (U,Mo)Al4 phase. Growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…During reactor operation, diffusion occurs producing intermetallic compounds with physical and thermal properties that cause adverse effects on the performance of the materials. [6,8] The reaction layer between the U-Mo and the Al matrix experiences significant volumetric expansion that causes fracturing. [9] Moreover, these compounds have lower thermal conductivities than desired, which results in heat buildup in the fuel particles that in turn accelerates the interdiffusion processes between the U-Mo and the Al alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During reactor operation, diffusion occurs producing intermetallic compounds with physical and thermal properties that cause adverse effects on the performance of the materials. [6,8] The reaction layer between the U-Mo and the Al matrix experiences significant volumetric expansion that causes fracturing. [9] Moreover, these compounds have lower thermal conductivities than desired, which results in heat buildup in the fuel particles that in turn accelerates the interdiffusion processes between the U-Mo and the Al alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Moreover, these compounds have lower thermal conductivities than desired, which results in heat buildup in the fuel particles that in turn accelerates the interdiffusion processes between the U-Mo and the Al alloys. [8,10] The growth and properties of the intermetallic compound layers that develop in the U-Mo/Al system must be controlled in order to improve the functionality and service life of the fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Keiser et al, [22] Palancher et al, [25] and Perez et al [23,28] reported concentration profiles of sufficient thickness to permit analysis, by energy dispersive spectroscopy (EDS) and EPMA, of the interaction layer. Concentration profiles of U, Mo, and Al show negligible gradients with near constant concentrations, particularly for Al throughout the interdiffusion zone thickness.…”
mentioning
confidence: 98%
“…Perez et al [23] annealed a series of diffusion couples of U-Mo vs pure Al (99.999 pct) at 823 K (550°C), and determined the (U,Mo)Al 4 as the average composition of the interdiffusion zone based on electron probe microanalysis (EPMA). Mirandou et al, [24] Palancher et al, [25] and Mazaudier et al [26] observed, in addition to the (U,Mo)Al 3 and (U,Mo)Al 4 phases, the U 6 Mo 4 Al 43 and UMo 2 Al 20 ternary intermetallic phases, along with the cfi(a+d) decomposition of the U-Mo alloy.…”
mentioning
confidence: 99%
“…Diffusional interactions in the U-Mo-Al system have been extensively studied through diffusion-couple experiments [1][2][3][4][5][6][7][8], alloy casting and characterization [9,10], and characterization of U-Mo dispersions in Al matrix and monolithic plate assemblies encased in Al alloy [4,5,[11][12][13][14][15][16][17][18]. The studies have been carried out to support the Reduced Enrichment for Research and Test Reactors (RERTR) program [13] for the development of low-enriched U-Mo fuels encased in Al [13,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%